PROFITABILITY ANALYSIS PT. HERO SUPERMARKET TBK AFTER CONVERTING GIANT TO IKEA - Nugrainda, Auliah; Anwar; Tenri Sayu Puspitaningsih Dipoatmodjo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the financial performance at PT. Hero Supermarket Tbk for the 2018-2022 period using quarterly, using the Return on Investment ratio, and the Return on Equity ratio using the Du Pont System approach. The population in this study is the entire financial report data of PT. Hero Supermarket Group Tbk taken from the Indonesian Stock Exchange (IDX) website. The sample of this study uses time series data for the last five years consisting of quarterly balance sheets and profit and loss reports from PT. Hero Supermarket Group Tbk Period 2018-2022. Data collection techniques for this study using documentation techniques, which include data collection in the form of quarterly financial reports for the last 5 periods of PT. HERO Supermarket Group Tbk on the company's official website listed where it aims to collect and analyze financial report data and then perform a profitability ratio analysis. From the results of this study, we can see that the impact of converting Giant to IKEA for now looks influential but is still not clearly visible or not significantly visible. To see the results of the significant profitability ratios of PT Hero Supermarket Group Tbk, it takes 2 to 3 years.